Intravitreal Ranibizumab versus Razumab in treatment naïve diabetic macular edema - Dhandapani A; Ravindran S; Muthusamy K; Muruganandham K; Kaliamurty S (Journal of Medical and Scientific Research)
Background: Diabetic macular edema (DME) is a leading cause of vision impairment globally among working population, with anti-vascular endothelial growth factor (anti-VEGF) therapies being the standard treatment. The high cost of anti-VEGF drive use of biosimilars like Razumab®. This study provides a prospective real-world comparison of innovator ranibizumab and Razumab® in treatment-naïve DME patients, addressing the current gap in comparative data.